Pendidikan Islam dan Pembelajaran Karakter Dalam Konteks Globalisasi - Mardiah Astuti; Herlina Herlina; Imelda Agustina; Annisa Winada; Muhammad Alfaizi (Pusat Riset dan Inovasi Nasional, 2023)
The article entitled Islamic education and character learning in the context of globalization was written with the aim of forming individuals to have good character and morality. Character education is needed in a person because with good character a good and moral person is created. Character learning of course will create a person's character based on what is learned, so that the character will stick in him and even form identity in the future. In the current era of modernization, character education can be carried out through Islamic-oriented learning, so that even though one lives in the era of globalization, one can still maintain Islamic values embedded in oneself. This research was conducted using two methods, namely qualitative research through questionnaires and literature studies by looking at previous studies whose theme is of course related to the title of this article.